Patient safety curriculum development for undergraduate dentistry student - a critical analysis - Navarette, Napoleon Samson (Manila : National University, 2013)
The tasks ahead of health-care are immense and require all those involved in care to understand the extent of harm to patients and why health care must move to adopt a safety culture. Health care students, as future health care providers leaders, must prepare themselves to practice health care.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.